O Marquês de Pombal e a construção do ensino de primeiras letras (1757-1772) - Bispo, Matheus Luamm Santos Formiga (2021)
The overall objective this work is to understand the conception of teaching first letters based on the Pombaline legislation and policy through its constitution and practice, starting from Pombal and his men in the common action they undertook, emphasizing that elementary education was coordinated with secundar education, and this one with collegue education. We will make use of historiography, manuscripts and other documentary and legislative sources, as well as compendiums and periodicals published in the period. The primary sources - manuals and compendiums - are highlighted in the composition of the study, forming a panegyric of the precursors of the first letters, until then, the Marquis of Pombal. The selected chronological section starts in 1757 with the publication of the Law of Directory, known as the Indian Directory that institutes the teaching of the Vernacular language in the country, and ends with the law from November 6, 1772, which regulates the creation and administration of the Minor Schools. It was concluded that the pioneering action of the Marquês de Pombal would be, strictly, not so much in the introduction of State education, but in the proposal to elevate such Minor Studies with the scope of using this resource as a strategy for national strengthening and that the teaching of first letters appears before the Marquês de Pombal with the action of religion, contributing to social formation based on elementary knowledge.